2011
DOI: 10.1088/0022-3727/44/27/274010
|View full text |Cite
|
Sign up to set email alerts
|

Selective conversion of methane to synthetic fuels using dielectric barrier discharge contacting liquid film

Abstract: This paper presents the reaction mechanism of single-step methane partial oxidation to methanol at room temperature using non-thermal plasma microreactor. Macroscopic quantities of hydrogen peroxide (H2O2) and methyl hydroperoxide (CH3OOH) are produced when methane is partially oxidized at room temperature (about 5 °C). CH3OOH is known to be the principle intermediate of incomplete methane oxidation product such as CH3OH and HCHO, but has not been demonstrated experimentally so far. H2O2 promotes post-plasma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…The low CO 2 conversions may also be the result of the water gas shift (WGS) reaction as shown in Equation (14). Previous study suggested that an appropriate combination of plasma and catalyst could enhance the WGS reaction at low temperatures 48. In our study, it is interesting to note that fully packing different materials into the discharge gap leads to an increase in H 2 /CO molar ratio and a decrease in the selectivity of CO in comparison to the plasma dry reforming reaction with no packing material, which confirms the enhancement of the WGS reaction.…”
Section: Resultssupporting
confidence: 82%
“…The low CO 2 conversions may also be the result of the water gas shift (WGS) reaction as shown in Equation (14). Previous study suggested that an appropriate combination of plasma and catalyst could enhance the WGS reaction at low temperatures 48. In our study, it is interesting to note that fully packing different materials into the discharge gap leads to an increase in H 2 /CO molar ratio and a decrease in the selectivity of CO in comparison to the plasma dry reforming reaction with no packing material, which confirms the enhancement of the WGS reaction.…”
Section: Resultssupporting
confidence: 82%
“…On the other hand, in the 70/30 CH 4 /O 2 gas mixture, these reactions are negligible compared to the three-body recombination reaction with O 2 molecules, forming CH 3 O 2 radicals (see figure10(b)). This is in good agreement with Nozaki et al40 and Goujard et al41 , who also discussed the importance of the formation of CH 3 O 2 in the methane partial oxidation mechanism towards the formation of (c) Formation of syngas In Figure 11(a) and figure 11(b) the most important channels for production and loss of CO in a 70/30 CH 4 /CO 2 and a 70/30 CH 4 /O 2 gas mixture are illustrated, respectively. 90% of the CO formation occurs through the reaction of O 2 molecules with CHO radicals.…”
supporting
confidence: 93%
“…19,31,34,[86][87][88]97,98,102 and a much wider range of materials and applications are possible. 103,104 Here we will focus however only on the surface treatment of Si-ncs that have been presynthesized by electrochemical etching and dispersed either in water or ethanol. For the electrochemical etching process, similarly to our previous work, 105 we have used p-type borondoped silicon wafers (h100i, 0.1 U cm, thickness 0.525 mm).…”
Section: Laser-produced Plasmas and Electrical Discharge Plasmas In Contact With Liquidsmentioning
confidence: 99%